Season and size effects: changes in the quality of gilthead sea bream (Sparus aurata L.) - RODRIGUEZ, R.; FOUNTOULAKI, E.; GRIGORAKIS, K.; ALEXIS, M.; FLOS, R. (Mediterranean Marine Science, 2010)
The aim of this study was to investigate the potential effects of the harvesting season and fish size on the final quality of cage farmed gilthead sea bream (Sparus aurata). Morphometric analysis, fat stores estimation, fillet composition analysis, fillet fatty acids profile determination and sensory analysis were carried out on a commercially-sized cage farmed gilthead sea bream (Sparus aurata L.) population in April, June, July and November. Both season and size had a significant effect in morphometric characteristics. The most pronounced size effect was the change of fish shape, becoming rounder with fish growth, the increase of filleting yield and condition index. An increase of both peritoneal and perivisceral fat was observed in summer months. In general size had little effect on muscle composition. A significant size effect was observed in the fillet lipid content, which increased with it. Fillet lipid content was unexpected lower in the warm period (June-July). This can be possibly attributed to feeding restrictions that may have occurred, due to anoxic incidents related to high temperatures. Slight seasonal differentiations occurred in the muscle fatty acids. No significant differences were found in the organoleptic characteristics of the two size groups compared.